Screening for genetic haemochromatosis in blood samples with raised alanine aminotransferase. Issue 5 (1st May 2000) - Bhavnani, M; Lloyd, D; Bhattacharyya, A; Marples, J; Elton, P; Worwood, M
Abstract : BACKGROUND: In the UK approximately 1 in 140 people are homozygous for the C282Y mutation of the HFE gene and are at risk from iron overload caused by genetic haemochromatosis (GH). Early detection can prevent organ damage secondary to iron deposition and increase life expectancy. AIM: To screen for GH in all blood samples sent to the laboratory for routine liver function tests in which raised serum alanine aminotransferase (ALT) activity was detected. METHODS: ALT was measured in sera sent to the laboratory for routine liver function tests. In those samples found to have raised activity, transferrin saturation and ferritin were measured followed by genetic testing when transferrin saturation was increased. RESULTS: Of the 35 069 serum samples assayed for routine liver function tests, 1490 (4.2%) had raised ALT levels (>50 u/l). Transferrin saturation and serum ferritin concentrations were measured in these patient samples, and in 56 transferrin saturation was >60%. Further blood samples were requested from these patients for genetic testing: 33 samples were obtained. There were nine patients homozygous for the C282Y mutation of the HFE gene and three compound heterozygotes (heterozygous for both C282Y and H63D mutations). CONCLUSIONS: The association of raised ALT activity and transferrin saturation of >60% could provide a simple, cost effective method for detecting individuals with clinical haemochromatosis. Although many patients with GH may have been missed, this study suggests that the clinical penetrance of the disorder may be much lower than is generally supposed and that genetic screening will identify many people who may never develop clinical haemochromatosis.